The Influence of Leadership and Training on Employee Performance PT Prima Karya Sejahtera - Widia Astuti (International Journal of Integrative Sciences, 2023)
This research turned into carried out to recognize leadership and education on worker performance at PT Prima Karya Sejahtera. This examine uses a descriptive quantitative method of analysis with a survey technique, questionnaires, and interviews. The populace in this have a look at were all employees of PT Prima Karya Sejahtera, totaling 50 people using a saturated pattern. The evaluation method makes use of a validity test, reliability take a look at, multiple linear regression analysis, a couple of correlation coefficient, t-take a look at and f-test, and analysis of the coefficient of determination. based on the calculation consequences of multiple regression evaluation acquired Y = eleven.461 + zero.006 X1 + 0.711 X2, where is the employee overall performance (Y), management (X1), and schooling (X1) were examined using the t-take a look at indicating that the 2 impartial variables affect worker performance (Y) because the based variable. Then through the take a look at, the coefficient of determination suggests an R of zero.470 which means that there is a superb and robust relationship among leadership and training on worker overall performance. The coefficient of dedication is 0.202. This suggests 20.2%, while 79.8% is prompted by way of different elements inclusive of worker placement, paintings stress, paintings surroundings, and others. primarily based at the hypothesis checking out that changed into finished the usage of the f test, it become determined that remember = 21.980 and after consulting with the desk at a giant level of 5% and n = (-three) showed stable = 3.20, which means that that there may be a high-quality affect among management and education on performance employees because count number (21.980) > (3.20)